KNOWLEDGE AND MANAGEMENT OF MENSTRUAL PROBLEMS AMONG FEMALE STUDENTS OF YAGONGWO COLLEGE OF NURSING SCIENCES, KUJE, ABUJA, NIGERIA - UDOUDO INEMESIT OSCAR; IGWENWANNE EMA AMAKA; IYHOBHEBHE DAVID VICTOR; OBIOHA KENECHI UGONWA (Journal of Health Systems Research, 2026)
Menstrual problems are abnormalities affecting the menstrual cycle. Abdominal pains, irregular timing , heavy bleeding or absence of menstruation are common forms. The study assessed the level of knowledge of menstrual problems, examined students’ experiences and identified management practices. A descriptive research design was adopted for the study. The population was female students of Yagongwo College of Nursing Science, a sample size of 232 respondents was selected. A structured questionnaire was the instrument used for data collection. Descriptive statistics such as frequencies, percentages, mean, and grand mean were used for analysis. The findings revealed that respondents had a good level of knowledge of menstrual cycle and menstrual problems. However, a significant number of students experience menstrual problems such as lower abdominal pain (dysmenorrhea), fatigue, headaches, and irregular menstrual cycle. Different management methods were also identified in the study. The study concluded that although students possessed good knowledge and adopted relatively appropriate management practices, menstrual problems remain prevalent and continue to affect students’ academic and daily activities. It was recommended that menstrual health education be strengthened, school health services be improved, and students should be encouraged to adopt appropriate health seeking behaviors.